EFFECTIVENESS OF DEXAMETHASONE IN INTRA AND POST OPERATIVE PAIN MANAGEMENT OF UNILATERAL INGUINAL HERNIA SURGERY - Bashir Ahmed; Hamid Raza; Kamlaish (Journal of University Medical & Dental College, 2016)
ABSTRACT: OBJECTIVE: The aim of our study is to compare Fentanyl(1 micro/kg) alone, with fentanyl (0.75 micro/kg) administered with dexamethasone (8 mg), for the relief of pain in patients who are being operated for inguinal hernia repair. And compare the resulting analgesia using visual analog scale and hemodynamic variables. MATERIAL AND METHODS: The type of study is a randomized double blind case control study conducted for a period of one year from April 2013 to May 2014 at a tertiary care hospital in Karachi Pakistan. Patients diagnosed with inguinal hernia were admitted in the hospital. The patients were divided into two groups using a random number generator. Group A was selected to be given fentanyl 1 micro/kg−1 (control group) and the study group ( group B )to be given 8 mg dexamethasone with fentanyl 0.75 micro/kg−1 . Assessment of pain was based on hemodynamic changes intra operatively and visual analogue scale post operatively. The data was analyzed using SPSS version 20. RESULTS: In the control group, the hemodynamic variables including heart rate and blood pressure as compared with that of the study group (taken at 1, 5, 20 and 30 min after incision was given ) were considerably higher (P ≤ 0.001) . Intra-operative (rescue) analgesia that was required in the control group was n= 40 (100% ) while n= 24 (60%) for study group. The mean scores for pain measured at pre determined and ﬁxed time intervals were signiﬁcantly lower in the study group as compared to the control group ( p<0.001 ). The use of post operative (rescue) analgesia that was required was found to be n=40 (100% ) patients in the control group, while it was required in n= 30 ( 75% )patients in the study group. CONCLUSION: Administration of Dexamethasone 8mg IV with fentanyl reduces intra and post operative pain in the 1st hour after unilateral inguinal hernia repair, as compared to administration of fentanyl alone.